Disaster recovery plans and corporate governance in the banking sector of Iloilo City, Philippines - Aguillon, Emmanuel; De la Cruz, Maria Wila; Legara, Georgia Christine; Limsui, Divine Antoinette
In the business world, disasters are ever-present. Alongside the growth of several corporations and the fast paced technologicl advancement came the crises that destroyed the valuable outputs of man's hard work - money, establishments, jobs, people, and information. All so beacuse most have not thought of a doomsday to come, and thus have not prepared with what to do when the disaster strikes. A disaster recovery plan has become so popular ever since the two highlights of all disasters occurred and destroyed a number of corporations - the Y2K and the 9/11 terrorist attacks. Since then, many businesses shifted their attention to contingency plans so they can ensure that their operations will run smoothly at the event of a disaster. Disaster recovery is of particular importance for the banks in a locality hit by crisis - more so than other businesses - because their services are in great demand during times of community disaster. The average bank is multi-platformed, with multiple locations and varied operations and computer applications. It is an investment center where people put in their money hopin that it will grow through time. The descriptive study aimed to determine whether the disaster recovery schemes of banks in Iloilo City influence corporate governance. Conducted from December of 2006 to March of 2007, the researchers obtained information from key informants of five banks in the locale. The statistical tools used such as frequency distribution tables and formulae substitutions of SPPS, truly aided the researchers in knowing the relationships of the variables. The results showed that the disaster recovery scheme i.e. data protection, hardware facilities and human resources influences corporate governance specifically in aspects of the level of confidence, the quality of operations, the internal management and the stakeholder relation. Moreover, findings reveal that the level of information provided by the DRP Developer influences corporate governance in the same aspects.